Peran volunteer dalam mengembangkan Program International Office Voluntary Program (IOSVOLP) di UIN Salatiga - Rahmawati, Septiana Ery; Nabila A.B.A, Fikiy; Haniff, Haikal Akhtar; Lina, Marisa Fran; Ningsih, Dwi Cahya; Martatik, Bekti; Tiyarningrum, Adinda Nisaa; Destia, Maretha; Karimah, Lu’luun Najwal; Al Hamasi, Zufarul Haq (Tintamas: Jurnal Pengabdian Indonesia Emas, 2025)
The International Office Voluntary Program (IOSVOLP) at UIN Salatiga plays a strategic role in supporting the internationalization of higher education through active student involvement as volunteers. This program focuses on assisting international students in academic and non-academic adaptation while promoting Islamic values such as khidmah (service), ikhlas (sincerity), and amanah (responsibility). Using the Participatory Action Research (PAR) method, the program fosters collaboration among students, the institution, and the international community. Results show that volunteers significantly strengthen international services, cultural exchange, and the university’s global networking, contributing to Sustainable Development Goals (SDGs) such as quality education, reduced inequalities, and peace-building. Challenges encountered include communication barriers and cultural differences, which are addressed through structured training, cultural introduction, and language support. The study highlights the need for a sustainable volunteer development system, including regular training and evaluation, to ensure both technical competence and value-based awareness. IOSVOLP is expected to serve as a professional and globally oriented campus volunteerism model rooted in Islamic values.